2018
DOI: 10.48550/arxiv.1803.03040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carleman estimates and boundedness of associated multiplier operators

Abstract: Let P(D) be the Laplacian ∆, or the wave operator . The following type of Carleman estimate is known to be true on a certain range of p, q:The estimates are consequences of the uniform Sobolev type estimates for second order differential operators due to Kenig-Ruiz-Sogge [15] and Jeong-Kwon-Lee [13]. The range of p, q for which the uniform Sobolev type estimates hold was completely characterized for the second order differential operators with nondegenerate principal part. But the optimal range of p, q for whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…which is uniform in v ∈ R d . Later, the range of p, q on which the uniform Sobolev inequality (1.8) and Carleman inequality (1.9) hold was completely characterized in [13] and [14], respectively, where the authors proved that both (1.8) and (1.9) hold if and only if 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…which is uniform in v ∈ R d . Later, the range of p, q on which the uniform Sobolev inequality (1.8) and Carleman inequality (1.9) hold was completely characterized in [13] and [14], respectively, where the authors proved that both (1.8) and (1.9) hold if and only if 2…”
Section: Introductionmentioning
confidence: 99%
“…If we consider the Laplacian ∆ R d instead of , the ranges of p, q for the uniform Sobolev and Carleman inequalities do not coincide. We refer the interested readers to[14] for details.…”
mentioning
confidence: 99%
“…In [18] it was shown that, for any d ≥ 3 and v ∈ R d \ {0}, the Carleman estimate (1.7) holds if and only if…”
Section: Introductionmentioning
confidence: 99%
“…Such difference in the boundedess is attributed to different size of sets which carry singularities of the relevant Fourier multipliers. See [18] for more details.…”
Section: Introductionmentioning
confidence: 99%
“…We refer the reader forward to Section 2 for the definition of the spaces X estimate of the form e v•x ∇u L q ≤ C e v•x ∆u L p when d ≥ 3. See [22,3,46,21]. To get around the difficulty averaged estimates over O d and τ were considered ( [20,34,18]).…”
Section: Introductionmentioning
confidence: 99%